Reforma trabalhista: análise sobre a tramitação da lei 13.467/17 e suas implicações na consolidação de um estado democrático de direito - Waclawovsky, Luciana Elisabeth (2020)
This study aims at describing the developments amongst Brazil`s Legislative and Executive branch which resulted in the approval of the Labor Reform and the new labor legislation in November of 2017 – Law number 13.467/2017 –, and to underline labor discussions at the light of the Human Rights` perspective. Imposed by the business sector as an economic measure to guarantee the workers job security, as well as - according to employers` justifications - to increase the number of job opportunities, the reform promoted the alteration of more than 100 articles that constituted the Consolidation of Labor Laws (CLT), resulting in a deregulation of the labor hiring model, which previously assured – minimally – juridical and social security to Brazilian workers. Thus, the study gathers a theoretical approach to democracy, citizenship and human rights, discussing liberal State reforms, which eliminate primary investments and promote the extinction of both governmental subsidies and public policies as resolution to economic issues, without measuring the social impacts of the implementation of a minimal State. According to this research, these measures deepen social inequalities in a delicate moment in global history in which work relations face profound transformations. Therefore, this study contextualizes, historically, the surge of labor protection laws in Brazil, as well as discusses citizenship and the access to fundamental rights, as the right to a professional occupation, guaranteed in Brazilian Federal Constitution of 1988. Additionally, the study aims at bringing to discussion the nation’s political moment in which the Labor Reform was approved, through a theoretical dialog about how the law went through the National Congress. Through the analysis hereby presented, this study aims at stimulating a critical reflection about the courses of new work relations proposed by the Labor Reform, given that studies point at the generation of precarious work stations, besides a social setback that was previously considered impossible to occur, given our constitutional social rights and International Pacts. Additionally, the present work incorporates the first impressions on the pandemics that paralyzed both the Western and Eastern world during the first semester of 2020.